Pengaruh Etika Bisnis Islam dan Kualitas Produk Terhadap Kepuasan Konsumen pada Usaha Lontong Pak Muslim - Reza Aliyanda; Ira Mayasha; Raihani Fadila; Ahlamul Jaris; Ridho Laksamana Fajri; Pani Akhiruddin Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the influence of Islamic business ethics and product quality on consumer satisfaction in the culinary business Lontong Pak Muslim in Medan. Islamic business ethics in this study are measured through the application of principles such as honesty, trustworthiness, and fairness, while product quality includes taste, cleanliness, and authenticity of raw materials. This research method uses a quantitative approach with data collection through a Likert scale-based questionnaire distributed to 100 respondents. The data analysis technique used is multiple linear regression, with t-test, F-test, and coefficient of determination to see the relationship and influence between variables. The results of the study indicate that Islamic business ethics and product quality partially and simultaneously have a positive and significant effect on consumer satisfaction. Product quality has a more dominant influence than Islamic business ethics, indicating the importance of taste quality and cleanliness in increasing customer satisfaction. Overall, this study shows that the application of business ethics in accordance with Islamic values ​​and good product quality can strengthen consumer loyalty and maintain business sustainability. These findings provide recommendations to culinary business actors to continue to pay attention to product quality and uphold the principles of Islamic business ethics in an effort to increase consumer satisfaction and competitiveness in the market.